Stilistika Prosa Dalam Buku “Sang Nabi” Karya Kahlil Gibran - Arpina, Arpina; Iskandar, Iskandar; Hamsa, Hamsa (Al-Syamail: Jurnal Bahasa dan Sastra Arab, 2025)
Literary works are the product of an individual’s creativity created for enjoyment; each author has their own way of expressing ideas and depicting them through a distinctive linguistic style. The stylistic devices found in the prose The Prophet by Kahlil Gibran serve to help analyze and give a complete picture of the value and meaning of each sentence in that prose. These include comparative figures of speech (association, personification, anthropomorphism, metaphor, periphrasis), contrasting devices (hyperbole, irony, sarcasm), and emphatic devices (climax, rhetorical question). This study is classified as library research. The data‑collection technique began with repeatedly reading the prose under study, comprehending its content, finding books related to the research topic for reference, selecting several prose passages from Kahlil Gibran’s The Prophet, and analyzing each sentence containing a stylistic device using a descriptive qualitative method. The results of the study on the use of stylistic devices in Kahlil Gibran’s The Prophet reveal ten different types of figures of speech, organized into three categories: comparison, contrast, and emphasis. The distribution is as follows: association in 21 sentences; personification in 40 sentences; anthropomorphism in 4 sentences; metaphor in 2 sentences; periphrasis in 2 sentences; hyperbole in 3 sentences; sarcasm in 1 sentence; irony in 1 sentence; climax in 2 sentences; and rhetorical question in 6 sentences. The most frequently used device in The Prophet is personification, appearing in 40 sentences.